2022
DOI: 10.1111/cup.14238
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic features of necrobiosis lipoidica

Abstract: Background Necrobiosis lipoidica (NL) is an uncommon granulomatous dermatosis that can occur in patients with or without associated diabetes mellitus (DM). Prior studies have attempted to determine distinctive histopathologic features of NL in patients with and without DM. Methods A retrospective review of 97 patients with NL was performed to determine the similar and distinctive histopathologic features in patients with DM and without DM. Results Of the 97 patients, 32% (n = 31) had DM. Epidermal acanthosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…1,3 It has been suggested that there are different pathogenetic drivers of NL in patients with DM and those without DM, and distinctive histopathologic features of these groups have been reported. 1,8,21 Specifically, NL patients without DM have more frequent naked (sarcoidal/tuberculoid) granulomas (23% vs. 3%), more frequent eosinophils (39% vs. 10%), more frequent acanthosis (32% vs. 12%), and less frequent neutrophilic infiltration (18% vs. 45%) compared to NL patients with DM. 21 These prior studies have not investigated whether different histopathologic findings correspond to differences in ulceration rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3 It has been suggested that there are different pathogenetic drivers of NL in patients with DM and those without DM, and distinctive histopathologic features of these groups have been reported. 1,8,21 Specifically, NL patients without DM have more frequent naked (sarcoidal/tuberculoid) granulomas (23% vs. 3%), more frequent eosinophils (39% vs. 10%), more frequent acanthosis (32% vs. 12%), and less frequent neutrophilic infiltration (18% vs. 45%) compared to NL patients with DM. 21 These prior studies have not investigated whether different histopathologic findings correspond to differences in ulceration rates.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, NL patients without DM have more frequent naked (sarcoidal/tuberculoid) granulomas (23% vs. 3%), more frequent eosinophils (39% vs. 10%), more frequent acanthosis (32% vs. 12%), and less frequent neutrophilic infiltration (18% vs. 45%) compared to NL patients with DM 21 . These prior studies have not investigated whether different histopathologic findings correspond to differences in ulceration rates 1,21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnson et al retrospectively reviewed 97 patients with NL, out of whom only 32% had DM. They found that histologically epidermal acanthosis was more commonly seen in diabetic patients, while naked granulomas were more frequently seen in patients without DM [ 6 ]. Our patient had no DM.…”
Section: Discussionmentioning
confidence: 99%
“…Although the diagnosis of NL is sometimes made on clinical examination alone, a biopsy may be required to distinguish NL from potential confounding diagnoses, including granuloma annulare, necrobiotic xanthogranuloma, sarcoidosis, diabetic dermopathy, and lipodermatosclerosis 2 . Histologically, NL is identified by horizontally palisaded granulomatous inflammation and necrobiosis 5 …”
Section: Introductionmentioning
confidence: 99%